effect of spraying with different concentrations of the growth regulator paclobutrazol on the yield characteristics of three varieties of oat crop Avena sativa L. - Baqer Hammood Ajeel, Baqer Hammood Ajeel; Abdul Amir Rahim (University of Thi-Qar Journal of agricultural research, 2024)
The experiment was conducted at the Research Station of the College of Agriculture, University of Basrah,located north of Basrah city, during the winter season of 2022-2023, in a loamy soil. The study aimed toinvestigate the response of three varieties of oats (Avena sativa L.) to foliar spraying with differentconcentrations of the growth regulator paclobutrazol. The study included three oat varieties (Ganzania,Shafa, and CarlIoup) under the influence of spraying three concentrations of paclobutrazol (25, 50, and100 mg/L) and a control treatment. The interaction between the two factors was also studied. Thespraying was carried out in two stages, the first at the beginning of branching, and the second after threeweeks from the first spray.The experiment was arranged using a randomized complete block design(RCBD) with three replicates. The results showed the superiority of the paclobutrazol treatment (50 mg.l-1), which recorded the highest averages for most of the studied yield characteristics, as the lowestaverage number of panicles m-2was recorded at 458.05 dalia - and the highest average number of grainsper dalia was 55.45 grains g-1, and the highest average weight was recorded. 1000 grains amounted to37.33 g, while the Ganzania variety was superior in terms of the number of days and the number ofgrains in of panicl and 1000 grains amounted to 458.05 and amounted to 55.45 grains in of panicl-1 and 34.93 g and its components, protein content in grains, and chlorophyll in leaves were studied. Theresults showed the superiority of the paclobutrazol treatment (50 mg/L), which recorded the highestmeans for most of the studied growth traits. It had the lowest average plant height, reaching 70.75 cm. Italso recorded the highest average chlorophyll content, reaching 143.90 mg/100 g, and the highest averagefor the number of tillers, reaching 488.97 tillers/m². Additionally, it recorded the highest average for stemdiameter, reaching 4.49 mm.